Evaluation of furnace performance in terms of thermal efficiency in the High Vacuum Unit Crude Distiller & Light Ends in the Oil Refinery Industry - Rizza Fadillah Fitri; Novia Novia; Nadia Nadia; Amrina Dwi Pratiwi (Fakultas Teknik Universitas Wahid Hasyim, 2025)
The main processes in an oil refinery are divided into primary processes (Crude Distillation Unit and Gas Plant) and secondary processes (HVU, RFCCU, and LEU), in which the HVU furnace heats the feed prior to vacuum distillation. Heat transfer within the furnace occurs via radiation and convection, with approximately 70% of the heat load absorbed in the radiant section and 30% in the convective section. The furnace performance evaluation was conducted by analyzing operational data from June 18 to July 17, 2025, using mass and energy balance methods. The calculation results indicate that the highest actual furnace efficiency was achieved on June 18, 2025, at 87.72%, exceeding the design efficiency of 85%. Variations in efficiency are influenced by several factors, including excess O₂ levels, fuel flow rate, final feed temperature, and the magnitude of heat loss in the flue gas. Significant heat losses can reduce furnace efficiency; therefore, routine maintenance is required, particularly on the Air Preheater (APH), to optimize the utilization of flue gas heat before it is released into the environment.